Microhabitat distribution of Pseudodactylogyrus anguillae and Pseudodactylogyrus bini among and within gill arches of the European eel (Anguilla anguilla L.) - Matejusová, Iveta; Simková, Andrea; Sasal, Pierre; Gelnar, Milan (Parasitology research, 2003)
The outlying mean index (OMI) method was used to test for seasonal microhabitat partitioning in Pseudodactylogyrus anguillae and Pseudodactylogyrus bini communities parasitising European eel ( Anguilla anguilla L.) in four seasons. No differences in the occurrence of parasites were found in different seasons or on different gill arches. The OMI analysis showed that hemibranch separation and gill segments were the main factors explaining the variation in parasite niche occupation for the first factorial axis, which was generally more significant than the second factorial axis. The OMI and tolerance indices were compared for both species in the seasons studied, and the main differences between species indices were recorded. P. anguillae and P. bini communities were partitioned in the seasons with high epidemiological parameters of the infection. In the seasons with low epidemiological parameters, or in seasons when the parasite species preferred gill arches, the characters of gill division (lower level of gill division than gill arches) were not important for the partitioning of the Pseudodactylogyrus communities.
Keywords: ploštěnci; ekosystém; Population Dynamics; Gills; Anguilla; Animals; populační dynamika; žábry; roční období; Seasons; Ecosystem; zvířata; Platyhelminths